Questions: Solve the radical equation. Check all proposed solutions.
x - sqrt(4x - 19) = 6
Select the correct choice below and, if necessary, fill in the answer box to complete your choice.
A. The solution set is .
(Use a comma to separate answers as needed. Simplify your answer.)
B. The solution set is ∅.
Transcript text: Solve the radical equation. Check all proposed solutions.
\[
x-\sqrt{4 x-19}=6
\]
Select the correct choice below and, if necessary, fill in the answer box to complete your choice.
A. The solution set is $\square$ $\}$.
(Use a comma to separate answers as needed. Simplify your answer.)
B. The solution set is $\varnothing$.
Solution
Solution Steps
Step 1: Isolate the Radical
Start with the original equation:
\[
x - \sqrt{4x - 19} = 6
\]
Isolate the radical term:
\[
-\sqrt{4x - 19} = 6 - x
\]
Multiply both sides by -1:
\[
\sqrt{4x - 19} = x - 6
\]
Step 2: Square Both Sides
Square both sides to eliminate the radical:
\[
4x - 19 = (x - 6)^2
\]
Expand the right side:
\[
4x - 19 = x^2 - 12x + 36
\]
Step 3: Rearrange to Form a Quadratic Equation
Rearrange the equation to set it to zero:
\[
0 = x^2 - 12x + 36 - 4x + 19
\]
Combine like terms:
\[
0 = x^2 - 16x + 55
\]
Step 4: Solve the Quadratic Equation
Factor the quadratic equation:
\[
0 = (x - 11)(x - 5)
\]
Set each factor to zero:
\[
x - 11 = 0 \quad \text{or} \quad x - 5 = 0
\]
Thus, the solutions are:
\[
x = 11 \quad \text{and} \quad x = 5
\]
Step 5: Check Proposed Solutions
Substitute \( x = 11 \) back into the original equation:
\[
11 - \sqrt{4(11) - 19} = 6
\]
Calculate:
\[
11 - \sqrt{44 - 19} = 6 \quad \Rightarrow \quad 11 - \sqrt{25} = 6 \quad \Rightarrow \quad 11 - 5 = 6
\]
This is valid.
Now check \( x = 5 \):
\[
5 - \sqrt{4(5) - 19} = 6
\]
Calculate:
\[
5 - \sqrt{20 - 19} = 6 \quad \Rightarrow \quad 5 - \sqrt{1} = 6 \quad \Rightarrow \quad 5 - 1 = 6
\]
This is not valid.